KEEFEKTIFAN MODEL PEMBELAJARAN STAD DAN CIRC DITINJAU DARI HASIL BELAJAR MATEMATIKA SISWA KELAS 4 SD - Purnomo ,; Wasitohadi ,; Theresia Sri Rahayu (Universitas Muhammadiyah Semarang, 2018)
AbstractThe purupose of this research was to investigate any significant differences between STAD and CIRC learning method reviewed from the fourth grade of elementary school in Merbabu cluster learning outcomes in Mathematic. The type of the research is quasi research. The samples were the fourth graders of SDN Jeruk 1 with 29 students for the first group of the research and SDN Tarubatang 1 with 25 students for the second group of the research. Technique used in this research were descriptive analysis technique and statistical analysis technique with t-test. The result of the tcount was 2,097 and the ttable was 2,007 with sig. (2-tailed) was 0,041. It indicated that the probability of the significant less than 0,05 so Ha was accepted and the H0 was rejected, it means there is a differences in significant influences between the STAD and CIRC learning method reviewed from the fourth grade of elementary school in Merbabu cluster learning outcomes in Mathematic. The result was support with the average of the result STAD was 76,03 and the CIRC was 62,59. Keyword : STAD, CIRC, and learning outcomes